Using Wattpad Platform To Improve Writing Skill Of The Tenth-Grade Students of SMA Negeri 2 Palu - Syahwalya, Fitra; Manurung, Konder; Patmasari, Andi; Mukrim, Mukrim (Universitas Negeri Padang, 2024)
The aim of this research aims to prove if the use of the Wattpad platform can improve the writing skills of the tenth-grade students of SMA Negeri 2 Palu. The research method is a quantitative method with a quasi-experimental design. To collect data, this study used pre-test and post-test. The subjects of this study were divided into two, the experimental group and the control group. The research instrument is a writing test with narrative text type.The results showed that the post-test t-counted value (6.608) was greater than the t table (1.670) by applying a significance level of 0.05 with degrees of freedom (df) = 64. Based on the results of the study, if the t value is greater than the t table, then H0 is rejected and Ha is accepted,.In other words, the effect of using Wattpad platform on students' writing skills has a significant effect.